1991
DOI: 10.1007/bf01279617
|View full text |Cite
|
Sign up to set email alerts
|

Redistribution of GAP-43 during growth cone developmentin vitro; immunocytochemical studies

Abstract: The growth-associated protein GAP-43 (B-50, F1, pp46), has been found in elongating axons during development and regeneration, and has also been associated with synaptic plasticity in mature neurons. We have examined the loss of GAP-43 labelling from cerebellar granule cells with immunocytochemical localization of a polyclonal antibody to GAP-43. One day after plating, the plasma membrane of cell bodies, neurites and growth cones were all labelled with anti-GAP-43. By 10 days, most of the cell body labelling w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

1991
1991
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 39 publications
1
12
0
Order By: Relevance
“…Selective distribution of GAP-43 in elongating axons is the result of developing neuronal polarity. During neuronal differentiation, GAP-43 protein is lost from the cell body, distributed to distal axons, and concentrated in growth cones (Burry et al, 1991(Burry et al, , 1992Goslin et al, 1988Przyborski and Cambray-Deakin, 1994). Transport of GAP-43 protein associated with vesicles from the cell body to growth cones has been well documented (Benowitz et al, 1981;Skene and Willard, 1981a,b,c).…”
Section: Hud and Gap-43 Mrna Role In Growth Conesmentioning
confidence: 95%
See 1 more Smart Citation
“…Selective distribution of GAP-43 in elongating axons is the result of developing neuronal polarity. During neuronal differentiation, GAP-43 protein is lost from the cell body, distributed to distal axons, and concentrated in growth cones (Burry et al, 1991(Burry et al, , 1992Goslin et al, 1988Przyborski and Cambray-Deakin, 1994). Transport of GAP-43 protein associated with vesicles from the cell body to growth cones has been well documented (Benowitz et al, 1981;Skene and Willard, 1981a,b,c).…”
Section: Hud and Gap-43 Mrna Role In Growth Conesmentioning
confidence: 95%
“…Expression of GAP-43 has been correlated with axon elongation in developing and regenerating neurons (Skene and Willard, 1981a). When axon growth cones reach their targets, the levels of GAP-43 protein fall as they stop elongation and form presynaptic terminals (Burry et al, 1991;Caroni and Becker, 1992;Meiri et al, 1986;Perrone-Bizzozero et al, 1986). Thus, GAP-43 expression is considered an excellent marker of active axonal growth during development and nerve regeneration.…”
Section: Introductionmentioning
confidence: 97%
“…Twenty-four hours after plating the medium was removed, and a suspension of dissociated hippocampal neurons in defined medium (see ''Microwell culture'' section) was seeded on monolayers of L-cells with or without NCAM-140 expression at a density of 5,000 cells/well. After 24 hr incubation at 37°C, 5% CO 2 , neurons were visualized using immunohistochemical staining for GAP-43 (Burry et al, 1991). Briefly, the cells were fixed for 30 min in 4% w/v paraformaldehyde in PBS, and then incubated in rabbit anti-GAP-43 antibodies (Mosevitsky et al, 1994) diluted 1:100 in PBS, 1% FCS, 0.1% BSA, 50 mM glycine, 0.02% NaN 3 , 0.2% saponin at 4°C overnight.…”
Section: Co-culture Of Rat Hippocampal Neurons and Mouse Fibroblastoimentioning
confidence: 99%
“…In cerebellar cultures, GAP-43 has been found in axons and growth cones (Burry et al, 1991). Thisstudy also showed transitional elements in cultures during the first week labelled for GAP-43.…”
Section: Transitional Elementsmentioning
confidence: 95%